2022
DOI: 10.1038/s42003-022-04286-9
|View full text |Cite
|
Sign up to set email alerts
|

Microgravity environment grown crystal structure information based engineering of direct electron transfer type glucose dehydrogenase

Abstract: The heterotrimeric flavin adenine dinucleotide dependent glucose dehydrogenase is a promising enzyme for direct electron transfer (DET) principle-based glucose sensors within continuous glucose monitoring systems. We elucidate the structure of the subunit interface of this enzyme by preparing heterotrimer complex protein crystals grown under a space microgravity environment. Based on the proposed structure, we introduce inter-subunit disulfide bonds between the small and electron transfer subunits (5 pairs), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“… The site-directed mutagenesis and electron paramagnetic resonance (EPR) spectrum has indicated that three Cys residues in the Cys-rich region in the large subunit constitute the 3Fe-4S cluster (3Fe4S), which is thought to mediate the ET between FAD and heme c moieties . Another partial 3D structure composed of large and small subunits and a truncated cytochrome subunit, leaving only one heme c moiety ( Bc GDHγα-trβ), was also elucidated (PDB ID: 8HDD) to support this discussion . However, the overall structure of the membrane-bound subunit, including heme c moieties responsible for the electrode-active site, remains unknown.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“… The site-directed mutagenesis and electron paramagnetic resonance (EPR) spectrum has indicated that three Cys residues in the Cys-rich region in the large subunit constitute the 3Fe-4S cluster (3Fe4S), which is thought to mediate the ET between FAD and heme c moieties . Another partial 3D structure composed of large and small subunits and a truncated cytochrome subunit, leaving only one heme c moiety ( Bc GDHγα-trβ), was also elucidated (PDB ID: 8HDD) to support this discussion . However, the overall structure of the membrane-bound subunit, including heme c moieties responsible for the electrode-active site, remains unknown.…”
Section: Introductionmentioning
confidence: 97%
“…42 Another partial 3D structure composed of large and small subunits and a truncated cytochrome subunit, leaving only one heme c moiety (BcGDHγα-trβ), was also elucidated (PDB ID: 8HDD) to support this discussion. 43 However, the overall structure of the membrane-bound subunit, including heme c moieties responsible for the electrode-active site, remains unknown. FDH is a particular enzyme with intense DET-type bioelectrocatalytic activity and has been extensively investigated from electrochemistry, protein engineering, and spectroscopy perspectives.…”
Section: ■ Introductionmentioning
confidence: 99%